Correlates of conflict resolution across cultures. (31st August 2021) - Garfield, Zachary H.
Abstract: Abstract: Conflicts are ubiquitous between individuals as well as between groups. Effective conflict resolution is essential for individual well-being and group functioning and often involves leadership dynamics. The evolutionary human sciences have suggested that conflict resolution is shaped by psychological heuristics, norms and ecology. There are limited empirical data, however, on conflict resolution across cultures. Using a cross-cultural database of 109 leadership dimensions coded from over 1200 text records from the eHRAF ethnographic database, exploratory analyses investigated correlates of conflict resolution. The results revealed greater evidence of conflict resolution among kin groups than political groups and greater evidence of within-group conflict resolution than between-group, which did not vary across subsistence strategies or group contexts, with two exceptions – military group conflicts were biased towards between-group contexts and religious groups biased towards within-group contexts. The strongest predictors of conflict-resolution services were other prosocial functions and included group representation and providing counsel, protection and punishment, as well as qualities of interpersonal skills and fairness. Followers received social service benefits and reduced risk of harm. For leaders who resolve conflicts, status and social benefits were potential negative predictors. These results provide a comparative view of the correlates of conflict resolution suggesting diversity across social contexts.